Nutritional requirements, chemical sensitivity, and in vitro growth of Rhizina undulata - Semashko, Iryna (2014)
Fire is an important factor for biological diversity in boreal forests. According to the FSC requirements, annually around 5% of the clear-cut forest territory in Sweden should be burned. On the other hand, fire is the triggering factor for the development of the pathogenic fungus Rhizina undulata, which causes considerable losses in planted coniferous seedlings on previously burned sites. The damage caused by the fungus can lead to the death of up to 80 % of coniferous seedlings. The aim of this study was to investigate nutritional and chemical preferences of the fungus. In the first phase the production of fungal material (mycelium, ascospores and conidia spores) in different conditions was examined. Only mycelium was found to be produced in amounts sufficient for further experiments. The preferred media was malt extract broth (MEB) maintained at room temperature without agitation. In the second phase, the ability of a fastgrowing R. undulata strain to utilize more than 285 different chemical substrates within carbon, nitrogen, phosphorus or sulfur groups was tested using Phenotype MicroArray technology. The utilization rates of carboxylic acids and nitrogen compounds were the highest among the tested groups. From a qualitative point of view, the group of carbon-dominated substances had the highest number of compounds utilized by the fungus. The approach used in this study can help to evaluate the qualitative and quantitative chemical traits that increase or decrease the risk for R. undulata damages in plant materials. In the long term, the approach could yield information that could potentially be used to formulate guidelines in tree-breeding for increased resistance to the fungus.